A novel heterozygous frameshift pathogenic variant in GCM2 gene causing isolated hypoparathyroidism: a case report - Onishi, Ayano; Obata, Yoshinari; Hayakawa, Tomoaki; Fujiwara, Makoto; Ohata, Yasuhisa; Tamura, Yuri; Kawata, Satoshi; Mukai, Kosuke; Miyashita, Kazuyuki; Yamamoto, Kenichi; Kubota, Takuo; Fukuhara, Atsunori; et al. (Frontiers in Endocrinology, 2025)
Glial cells missing transcription factor 2 (GCM2) is one of the genes responsible for isolated hypoparathyroidism. Most cases of hypoparathyroidism caused by GCM2 pathogenic variants result from homozygous or compound heterozygous loss-of-function variants, with only a limited number of heterozygous variants reported. A 24-year-old woman with recurrent tonic convulsions was admitted to our hospital. Laboratory findings revealed severe hypocalcemia (1.28 mmol/L), normophosphatemia (1.36 mmol/L), and low intact parathyroid hormone levels (0.84 pmol/L). Based on this, hypoparathyroidism was diagnosed. Comprehensive gene analysis using next-generation sequencing revealed a novel heterozygous frameshift pathogenic variant (c.1366delG, p.Ala456ProfsTer75) in the GCM2 gene (NM_004752.4). Sanger sequencing of the patient and parents confirmed de novo occurrence. This variant is predicted to exert a dominant-negative effect by impairing GCM2 function. This case provides further evidence that heterozygous GCM2 variants can lead to hypoparathyroidism. Additionally, it underscores the importance of genetic testing for hypoparathyroidism of unknown etiology even in adults.